METODE TRANSMISI GONG KEBYAR PADA KOMUNITAS KARAWITAN BALI DI SURAKARTA - Aulia, Riza Alif; Mulyana, I Nengah (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2023)
Gong Kebyar is one of the most popular gamelan ensembles from Bali. The distribution of Gong Kebyar is almost spread throughout the archipelago and even the world. One of them is in the city of Surakarta, which is rich and thick with Javanese culture and art. The rich and thick Javanese culture in Surakarta does not prevent Gong Kebyar from being able to grow and develop in this city. The transmission practice has been going on since the first time Gong Kebyar arrived in Surakarta until now. Groups or communities of Gong Kebyar took turns forming. Uniquely, the transmission practice is carried out to people who do not have a Balinese cultural background, in this case the majority are Javanese. Using the lens of traditional music transmission theory from Irawati which mentions three main elements in transmission practices namely actors, content, and mechanisms, this study aims to reveal the methods used by Gong Kebyar teachers in Surakarta in transmitting their knowledge to students from different backgrounds.